PLC system to optimize training device of upper limb spasticity / Nurul Atiqah Othman...[et al.] - Othman, Nurul Atiqah; Che Zakaria, Noor Ayuni; Mohd Ramli, Mohd Hanif (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This study provides an alternative to improvise the therapist education system by reaping the benefits of transferring industrial robotics precision into the medical and healthcare education. The proposed therapist education training simulator is driven and controlled by Programmable Logic Controller (PLC). It aims to innovate the systematic learning of physiotherapy skill sets in dealing with upper limb spasticity according to the module introduced in earlier research and publications. This research will introduce the combination of a clinical database of spasticity symptoms, the earlier work on this same simulator, and also human machine interface (HMI). This research is motivated by the purpose to avoid injury during therapy sessions due to the lack of skills and experiences of the trainee therapists. This research is to enhance the hands-on training of the trainee therapists with the proposed upper limb simulator before the real engagement with patients. This approach shows promising future improvement in therapist education strategies by combining Human Machine Interface Software Control and Data Acquisition (HMI SCADA) with PLC to further optimize the training device of upper limb spasticity simulator .